Optimal Planting Density of Taraxacum kok-saghyz Bred for Large Root Size: Seed, Latex, and Rubber Yields - Nathaniel P. King-Smith; Valerie M. Anderson; Aswathy Sasidharan Pillai; Judit E. Puskas; Katrina Cornish (HortScience)
The rubber dandelion, Taraxacum kok-saghyz (TK), produces similar quality natural rubber (NR) to Hevea but can be grown in temperate regions and could supplement the global supply chain, providing NR security to countries relying on imports. This study examines the effect of planting density on yield parameters uniquely using an advanced rubber dandelion accession bred for large root size in the field for eight generations. Plants were grown at densities of 0.31, 0.62, 1.23, and 2.47 million plants/ha in greenhouse planting boxes. The effects of planting density on plant growth, seed set, latex, and NR yields were compared with previous literature where seed from the US Department of Agriculture 2008 TK collection from Kazakhstan or from interbred plants of that collection were planted at different densities. Maximum seed production in the greenhouse environment was equivalent to 219 million seed per hectare. Latex concentration in processed roots ranged from 5.3 to 9.9 mg/g dry root. The weight average molecular weight of rubber from this investigation was sufficient for rubber product manufacturing (1255 to 1744 kg/mol) and did not differ significantly at different planting densities. A maximum rubber yield of 60 kg/ha in 4-month-old plants was attained at a density of 1.23 million plants/ha. This yield was lower than a previous report yet higher than several others and was therefore compared with all other TK planting density studies to assess the key factors that affect rubber yields in addition to planting density itself. High rubber yields were supported by high planting density, longer growing season, and late harvest in a single season. Optimal planting density must be determined for each distinct population, because advanced larger-rooted lines should be wider spaced than wild-type TK populations.